PENERAPAN PENDIDIKAN KARAKTER DI KALANGAN SISWA SEKOLAH - Gusti Vermata, Triani (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA, 2017)
In Indonesia, some school-aged children have violated the culture of the Indonesian nation, the lack of application of character education at home or at school causes them to do illicit acts or do not reflect school-aged children such as brawling among students, free sex, using drugs. Education value of the characters in order to form the successor of the nation of Indonesia who believe and piety to God Almighty and morals, knowledgeable, and become a democratic citizens and responsible is needed in order to form the successor of the Indonesian nation. Implementation of character education among school students is very helpful in establishing good character and praised by using strategies through learning, through extracurricular, through the development of school culture. Not only themselves and parents, the school also plays an important role in helping the implementation of character education to unform the character of students who are praised and obey Indonesian culture.